2010
DOI: 10.1186/1756-0500-3-82
|View full text |Cite
|
Sign up to set email alerts
|

GPs' decision-making when prescribing medicines for breastfeeding women: Content analysis of a survey

Abstract: BackgroundMany breastfeeding women seek medical care from general practitioners (GPs) for various health problems and GPs may consider prescribing medicines in these consultations. Prescribing medicines to a breastfeeding mother may lead to untimely cessation of breastfeeding or a breastfeeding mother may be denied medicines due to the possible risk to her infant, both of which may lead to unwanted consequences. Information on factors governing GPs' decision-making and their views in such situations is limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
0
36
0
3
Order By: Relevance
“…Many women use medicines during lactation, and health care providers face the challenge of determining which medications are compatible with breastfeeding. Although there is a large amount of literature on the availability of active components of medications in the breast milk, the quality of information about their safety during lactation varies and can be conflicting [9,10]; therefore, many women can be advised by health practitioners to stop breastfeeding unnecessarily or avoid treatment without evidence-based information [11,12]. For instance, there are several controversies regarding the safety of hormonal contraceptive medication use, which is widely used by women at this stage, during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Many women use medicines during lactation, and health care providers face the challenge of determining which medications are compatible with breastfeeding. Although there is a large amount of literature on the availability of active components of medications in the breast milk, the quality of information about their safety during lactation varies and can be conflicting [9,10]; therefore, many women can be advised by health practitioners to stop breastfeeding unnecessarily or avoid treatment without evidence-based information [11,12]. For instance, there are several controversies regarding the safety of hormonal contraceptive medication use, which is widely used by women at this stage, during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…One paper reported content analysis of open questions in a survey (31) and the fifth, (32) a non-peer reviewed report, covered perinatal mental health more generally. These papers were included due to the early stage of research in the area but their findings were used to support themes found in the other studies rather than initiating themes.Three papers focused on the postnatal period (28,29,31), one on pregnancy (30) and one on the "perinatal period" (32).…”
Section: Studiesmentioning
confidence: 99%
“…Após o parto, o uso de medicamentos é frequente entre as lactantes, devido à necessidade de tratamento para combater infecções, depressão, além das doenças crônicas que requerem medicamentos de uso contínuo (4)(5)(6) . Sabe-se que mais de 50% das mulheres que estão amamentando usam algum tipo de medicamento (7,8) .…”
Section: Objetivounclassified